2021
DOI: 10.1038/s41593-021-00825-5
|View full text |Cite
|
Sign up to set email alerts
|

Covert capture and attenuation of a hippocampus-dependent fear memory

Abstract: Reconsolidation may be a viable therapeutic target to inhibit pathological fear memories. In the clinic, incidental or imaginal reminders are used to safely retrieve traumatic memories of experiences that occurred elsewhere. However, it is unknown whether indirectly retrieved traumatic memories are sensitive to disruption. Here we used a backward conditioning procedure to indirectly retrieve and manipulate a hippocampus-dependent contextual fear engram in male rats. We show that conditioned freezing to a backw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 41 publications
(43 reference statements)
0
24
0
1
Order By: Relevance
“…This design may be applied to future work in humans seeking to assess the efficacy of protocols that enhance extinction 77 or modify the underlying fear memory trace through reconsolidation updating. 78 A further possibility to extend this work is to target engagement of activity patterns unique to formation of an extinction memory in distributed networks through closed-loop decoded neurofeedback 79,80 to create an enduring memory of safety. In this way, more precise localization of networks involved in organizing fear and extinction memory could ultimately lead to better treatments of psychiatric disorders like PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…This design may be applied to future work in humans seeking to assess the efficacy of protocols that enhance extinction 77 or modify the underlying fear memory trace through reconsolidation updating. 78 A further possibility to extend this work is to target engagement of activity patterns unique to formation of an extinction memory in distributed networks through closed-loop decoded neurofeedback 79,80 to create an enduring memory of safety. In this way, more precise localization of networks involved in organizing fear and extinction memory could ultimately lead to better treatments of psychiatric disorders like PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its expression in mouse brain cell lines, we also identified IL-22Rα expression in the hippocampus and cerebellum of C57BL/6 mice ( Figure 1 D). The hippocampus plays an important role in spatial memory and cognition, enabling information integration and transition from short-term memory to long-term memory [ 25 , 35 , 46 ]. In addition, the cerebellum is involved in motor control [ 32 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated the relevance of dorsal amygdala-hippocampus connectivity in contextual fear memory 11,14 , with some associating the level of amygdala -hippocampus connectivity to the long term retention of fear learning 15 . In a recent study, Ressler and colleagues showed that the hippocampus was involved in contextual fear memory and that inhibition of protein synthesis in hippocampal ensemble disrupted the reconsolidation of fear memories 52 . The authors argue that these findings might help us better understand real-life traumatic memories (which we study here).…”
Section: Discussionmentioning
confidence: 99%